Antibacterial Activities Test of the Xanthorrhizol Bioactive Compound in the Endophytic Bacteria of Curcuma xanthorrhiza - Utami, Ulfah; Fuadati, Choirul; Ida Alfiah, C. (International Journal of Engineering and Technology, 2019)
The objective of this study is to understand the potential of xanthorrhizol bioactive compound of the endophytic bacteria of Curcuma xanthorrhiza rhizome as an antibacteria  in vitro and the molecular docking simulation. The potency of two endophytic bacteria isolates (ET 1 and ET 2) as the antibacterial producer was tested, then the xanthorrhizol compound was separated using the Thin Layer Chromatography (TLC) and the contact-autobiography TLC.  Furthermore, a docking simulation analysis of the xanthrorrhizol compound as an antibacteria was made. The endophytic bacteria isolate ET1 shows its antibacterial activities to Escherichia coli (6.40 mm)  and Staphylococcus aureus (21.48 mm with the inhibiting power  under category of very strong), while the endophitic bacteria isolate  ET2 shows its antibacterial activities to E. coli (4.52 mm) and S. ureus (8.56 mm). The results of the bioautography -TLC test of the bioactive compound of the  endophitic bacteriais isolate ET1 (Rf 0.57) and isolate ET2 (Rf 0.57)  the visualization of 254 UV lamp is assumed to be the xanthorrizol compound, does not show  antibacterial activities in E. coli and S. aureus. Based on docking simulation results can be seen that xanthorrhizol compounds have the potential to interact with the target protein in  E. coli and S. aureus, but it   is lower than the control antibiotic.